Czy wojna w grach musi być zabawna? O wybranych grach planszowych z perspektywy poetologicznej - Brenskott, Krzysztof (Załącznik Kulturoznawczy, 2021)
Marco Arnaudo in Storytelling in the Modern Board Game: Narrative Trends from the Late 1960s to Today – through the lens of game studies and narratology – explores the synergy of board games, designers and players in story-oriented designs. A story can emerge from board game only in interactive and ergodic way, through synergy of game rules, material components and actions taken by players. The aim of this paper is to show that board games – which can be understood as transmedial narrative systems – could be studied on the grounds of poetics. How board games can use well known figures and methods of generating meaning, such as personification? What new we can learn about them in this new environment? Is it possible to adapt categories of immersion and emersion to board game studies? Recognition of board-game-specific ploys, such as physical changing and even destroying game components, can inspire us to look for similar solutions among literature, cinema or video games.